Are Consumers International? A Study of CSR, Cross-Border Shopping, Commitment and Purchase Intent among Online Consumers. Issue 4 (8th August 2019) - Anastasiadou, Eleni; Lindh, Cecilia; Vasse, Thibault
Abstract: The purpose of this study is to investigate purchase intent in online marketplaces as an international phenomenon. A profile of the international online consumer is established, taking into account factors such as indicators of socio-economic development of their home countries. A structural model is analyzed using LISREL, testing the importance of CSR, the propensity to buy from international online vendors and commitment with purchase intent as the dependent variable. A cross-national dataset of 804 respondents from 57 countries is analyzed, showing that CSR activities alone do not increase purchasing intent, but they do when mediated by commitment.